Pengaruh Persepsi Harga, Lokasi dan Promosi Terhadap Keputusan Menginap di Hotel Horison Bekasi - Laily Alfunnimah; Jamaludin Khalid (LPPM Universitas Asa Indonesia, 2022)
The purpose of this study is to investigate and analyze how perceptions of pricing, location, and promotions affect guests' choices to stay at Hotel Horison Bekasi. Testing Multiple regression is the analytical technique used to evaluate the hypothesis using test 1 and a sample of 100 respondents. collecting data via a survey with a Likert scale of 5 (five) possible responses. Non-probability sampling with accidental sampling is the data collection methodology used. Respondents who have at least once (once) visited and stayed at Hotel Horison Bekasi meet the accidental sampling requirements. The data analysis method made use of the SPSS version 20 program and the traditional assumption tests (Normality Test, Heteroscedasticity Test, Multicollinearity Test, and Linearity Test). The t test results revealed that location did not significantly influence the decision to stay, pricing perception significantly affected the decision to stay, and promotion significantly influenced the decision to stay. While the results of the f test indicate that there is a substantial interaction between the factors of perception of pricing, location, and promotion at the same time on the choice to stay at Hotel Horison Bekasi.